Forward looking dynamics in spatial CGE modelling - Johannes Bröcker; Artem Korzhenevych (Kiel Institute for the World Economy (IfW), 2011)
This paper sets up a multiregional dynamic framework by combining the optimal savings model with investment adjustment costs and the spatially disaggregated model with Dixit-Stiglitz structure in the modern sector. Because of increasing product diversity on the dynamic equilibrium path, the model belongs to the category of semi-endogenous growth models. The distinction of goods, factors, firms, and households by location, and the incorporation of trade costs in the model allow to study a variety of issues in regional and transport economics. We describe the model calibration and a taylor-made solution algorithm. The functionality is demonstrated using two illustrative examples.
Keywords: C68; D58; O41; R13; 330; spatial dynamic CGE modeling; multiple optimizing agents; transport costs